Platelet HLA gene bank digital matching technology for platelet transfusion refractory patients with malignant tumors: a case report - Gao, Xiang; Li, Jianhua; Ni, Xiuwen; Wang, Lijun; Hu, Peilin; Zhu, Xiaowei (Frontiers in Oncology, 2024)
The platelet human leucocyte antigen (HLA) gene bank contains the genetic information of HLA loci in a large number of blood donors. Currently, the most effective treatment for platelet transfusion refractoriness (PTR) is to evaluate the probability of antigenic mismatch by HLA genotyping of patients and to select HLA-matched donors in the gene bank through an information system. This case report describes the treatment of PTR in patients with malignant tumors using the platelet HLA gene bank digital matching technique. The analysis of individual cases will help guide transfusion strategies for such patients.